2020
DOI: 10.1159/000511225
|View full text |Cite
|
Sign up to set email alerts
|

The Experience of Lived Time in People with Dementia: A Systematic Meta-Synthesis

Abstract: <b><i>Introduction:</i></b> For people with dementia, lived time is important to understand, as the condition affects memory, perceptions of time, and life expectancy. The aim of this study was to locate, interpret, and synthesize the experience of lived time for people with dementia. <b><i>Method:</i></b> This article presents a qualitative systematic meta-synthesis. The theoretical framework of lifeworlds by van Manen provided the context for the study. The Cri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 80 publications
1
23
0
Order By: Relevance
“…For this systematic review, the data abstraction was conducted in line with the principles of an interpretative synthesis (Dixon‐Woods et al., 2005 ). The analyses were guided by inductive qualitative content analysis as described by Graneheim and Lundman ( 2004 ), which has been used in previous qualitative SRs (Eriksen et al., 2020 ; Sibbern et al., 2017 ; Uhrenfeldt et al., 2013 ). Conducting a qualitative content analysis gives the opportunity to interpret manifest and as well as latent content (Graneheim et al., 2017 ).…”
Section: Methodsmentioning
confidence: 99%
“…For this systematic review, the data abstraction was conducted in line with the principles of an interpretative synthesis (Dixon‐Woods et al., 2005 ). The analyses were guided by inductive qualitative content analysis as described by Graneheim and Lundman ( 2004 ), which has been used in previous qualitative SRs (Eriksen et al., 2020 ; Sibbern et al., 2017 ; Uhrenfeldt et al., 2013 ). Conducting a qualitative content analysis gives the opportunity to interpret manifest and as well as latent content (Graneheim et al., 2017 ).…”
Section: Methodsmentioning
confidence: 99%
“…They might also be afraid of not being able to comply with future wishes because of possible changes in the healthcare system (van der Steen et al, 2014;Wendrich-van Dael et al, 2020). It could also be the result of people with dementia primarily wanting to focus on living one day at a time (Eriksen et al, 2020) and a wish to live by the day (de Boer et al, 2012). A review by Sellars et al (2019) aiming to describe people with dementia and their carers perspectives on ACP, stated that planning for the future while living with dementia make the person confront emotionally difficult conversations and navigate existential tensions.…”
Section: Discussionmentioning
confidence: 99%
“…Most people with dementia express the need and wish to hold on to who they are and to be actively engaged in their own lives (Telenius et al, 2020). However, a dementia diagnosis seems to raise strong feelings of loss, uncertainty and worry about the future (Bunn et al, 2012;Eriksen et al, 2020;Mazaheri et al, 2013). Previous research has shown that people with dementia consider involvement in decision-making to be an important means of affirming self-identity (Caddell & Clare, 2010;Fetherstonhaugh et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Our study is the last study of four studies based on van Manen's theory comprehending lived relations, lived space, lived time and lived body (Eriksen et al 2016(Eriksen et al , 2020Førsund et al 2018). All interview-based studies of moderate to high quality published during a given period were included in this meta-synthesis.…”
Section: Strengths and Limitationsmentioning
confidence: 99%